Whips, Hammers, and Ropes: The Burden of Race and Desire in Clarke’s George & Rue - Hlongwane, Gugu D. (Studies in Canadian Literature, 2008)
George Elliott Clarke’s historical novel George & Rue (2005) recreates the murder of a white New Brunswick cabdriver by two black men, George and Rufus Hamilton, who were Clarke’s cousins. An application of postcolonial theories of violence, as elaborated by such thinkers as Frantz Fanon, and, more specifically, a critical stance engaged with the black Atlantic experience, reveals how Clarke’s novel blurs the line between perpetrator and victim within the context of Canadian racism in the first half of the twentieth century. George and Rue’s physical and spiritual hunger evokes desires for the white world that oppresses them, and their execution exposes the scales of justice that are never tipped in their favour.